Oxidative Dehydrogenation of Ethane to Ethylene with CO2 over Fe−Cr/ZrO2 Catalysts - Deng, Shuang; Li, Songgeng; Li, Huiquan; Zhang, Yi (Industrial & engineering chemistry research, 2009)
The catalytic performance of Fe−Cr/ZrO2 catalysts, prepared by two different methodscoprecipitation and coprecipitation−impregnation were examined in oxidative dehydrogenation of ethane to ethylene using CO2 as an oxidant. Thermogravimetric analysis and physicochemical characterization such as XPS, XRD, and BET were performed to explore the correlation of catalytic performance with physicochemical properties of the catalysts. Catalytic tests show that Fe−Cr/ZrO2 catalysts prepared by coprecipitation−impregnation have higher catalytic stability, higher CO2 conversion, and lower ethylene selectivity in comparison to Fe−Cr/ZrO2 prepared by coprecipitation. The characterization results indicate that the dehydrogenation of ethane is activated by Cr3+ species and Fe3O4 is formed during the reaction, which can promote the reverse WGS reaction. Coke deposition is the main reason of the deactivation of the catalysts. A possible reaction mechanism was proposed on the basis of these results.